Watermelon Democracy : Egypt's Turbulent Transition - Stacher, Joshua, 1975- (Book collections on Project MUSE., 2020)
""Watermelon Democracy" works from the premise that the 2011 uprising in Egypt and subsequent violent repression emerged from deep patterns in that country's modern history. By examining four aspects of the uprising, and juxtaposing actual events with findings in the literature, Stacher aims to explain aspects of the Egyptian case that the theoretical literature cannot"--